Rhabdomyomatous mesenchymal hamartoma of the left nare: A case report - Jacob M. Steiniger; Krishna G. Patel (Otolaryngology Case Reports, 2023)
Rhabdomyomatous mesenchymal hamartomas (RMH) are congenital benign skin masses that often present at birth and predominate in the head and neck. Superficially, masses appear to have a normal epidermal construct. Histologically, masses contain interspersed skeletal muscle fibers that may be associated with various mesenchymal elements such as adipose tissue, blood vessels, pilosebaceous units, and peripheral nerves. This case describes a 4-day-old male with an RMH of the left nare. Surgical resection as well as future cosmetic reconstruction associated with the patient's altered nasal anatomy is discussed.